Spontaneous pneumothorax and subcutaneous emphysema in COVID-19 patient: Case report (2020)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome virus coronavirus 2 (SARS-CoV-2). As known, COVID-19 has become a global pandemic and serious health problem. Disease mainly affects lungs and common findings are fever cough and shortness of breath. Computerized tomography (CT) has an important role in initial evaluation and follow up of COVID-19. Main (CT) finding of the disease is bilateral extensive ground-glass opacification (GGO) with a peripheral or posterior distribution, mainly involving the lower lobes. In this case report, we present a pneumothorax and subcutaneous emphysema case in a patient with COVID-19. To the best of authors’ knowledge, it is the first illustrated case of pneumothorax accompanying COVID-19 pneumonia. © 2020 Published by Elsevier Ltd on behalf of King Saud Bin Abdulaziz University for Health Sciences